Analysing laparoscopic management of adnexal masses in the adolescent females- A retrospective clinical trial in central indian population - Meena Naik; 1Shweta Rani Prasad; Shrikrishna Kumar Agrawal; Geetanjali Kanwar; Rekha Ratnani (International Journal of Health and Clinical Research, 2021)
Background: Adnexal masses affect approximately 5-10 percent of females and carry a risk of undergoing surgery at least once in a lifetime for ovarian masses. They are seen in females of all ages and can affect females in their older age from their adolescence to early fetus life.Aims: The present trial was carried out to assess histopathological findings, surgical procedure, and pre-operative diagnosis in adolescent females who were managed for adnexal masses by laparoscopic surgical procedure.Materials and Methods: The demographic data of 84 adolescent females were recorded and additional data obtained from the medical records were chief complaint, menstrual history and normalcy, radiographic size of the cyst detected on the ultrasound, pre-operative assessment, time of the surgery, surgical procedure, histopathological findings, and serum tumor markers. The collected data were subjected to the analyzation and the results were formulatedResults: The adnexal mass diameter in present study ranged from 2.5cm to 36cm. The mass of ˂10cm were recorded in 67.85% (n=57) of study subjects, and 5 subjects among these 57 had increased values of assessed tumor markers in serum. 6 (7.14%) masses among 84 subjects were greater than 15 cm diameter. HPE showed hemorrhagic cyst (9.52%, n=8), simple cyst (28.57%, n=24), or paratubal cyst (13.09%, n=11), polycystic ovary (2.38%, n=2), dermoid cyst (14.28%, n=12), cystadenoma, corpus luteal cyst (13.09%, n=11), hydrosalpinx (2.38%, n=2), and endometriotic cyst (1.19%, n=1).Conclusion: Laparoscopic management is an effective and safe technique for managing adnexal masses in adolescent females including large size cysts as most masses encountered during adolescence are benign.